Risk factors for perinatal mortality in an urban area of Southern Brazil, 1993 Fatores de risco para mortalidade perinatal em Pelotas, RS, 1993 - Ana M. B. Menezes; Fernando C. Barros; Cesar G. Victora; Elaine Tomasi; Ricardo Halpern; André L. B. Oliveira (Universidade de São Paulo, 1998)
INTRODUCTION: Although there was a considerable reduction in infant mortality in Pelotas, Rio Grande do Sul in the last decade, its perinatal causes were reduced only by 28%. The associated factors of these causes were analised. MATERIAL AND METHOD: All hospital births and perinatal deaths were assessed by daily visits to all the maternity hospitals in the city, throughout 1993 and including the first week of 1994. RESULTS: The perinatal mortality rate was 22.1 per thousand births. The multivariate analysis showed the following risk factors: low socioeconomic level, male sex and maternal age above 35 years . Among multigravidae women, the fetal mortality rate was significantly increased for mothers with a previously low birthweight and a previous stillbirth. For early neonatal mortality the risk was significantly increased by a smaller number of antenatal visits than 5 and low birthweight. CONCLUSIONS: Main risk factors for perinatal mortality: low socioeconomic level, maternal age above 35 years and male sex. For early neonatal mortality the risk was significantly increased by a smaller number of antenatal visits than 5 and low birthweight. INTRODUÇÃO: Apesar de importante redução da mortalidade infantil em Pelotas, RS, na última década, as causas perinatais foram reduzidas em apenas 28%. Analisou-se os principais fatores associados a essas causas. MATERIAL E MÉTODO: Todos os nascimentos hospitalares e óbitos perinatais, em Pelotas, foram acompanhados através de visitas diárias aos hospitais, durante 1993 até a primeira semana de 1994. RESULTADOS: O coeficiente de mortalidade perinatal foi 22,1/1.000 nascimentos. A análise multivariada apontou os seguintes fatores de risco: baixo nível socioeconômico, sexo masculino e idade materna acima de 35 anos. Nas multíparas, encontrou-se maior risco para a mortalidade fetal naquelas que relatavam baixo peso prévio e natimorto prévio. A mortalidade neonatal precoce esteve associada com número de consultas pré-natais inferior a 5 e baixo peso ao nascer. CONCLUSÕES: Principais fatores de risco para mortalidade perinatal: baixo nível socioeconômico, idade materna elevada e sexo masculino. Para mortalidade neonatal precoce, o risco maior foi para consultas pré-natais <5 e baixo peso ao nascer.